On the Irrelevance of Methodological Individualism - Gylys, Povilas (Ekonomika, 2017)
So far, methodological individualism has been the cognitive paradigm that permeates economic thinking in the epistemic community, in economic policy, and holds a place within the wide public at large. On the other hand, the tide of criticism addressed towards traditional economic philosophy is on the rise. The gist of this study is to demonstrate the weakness and antinomic character of the individualistic paradigm and to suggest an alternative worldview – methodological holism.
Keywords: methodological individualism; market fundamentalism; economy; methodological holism